AB0698 EFFECTIVENESS AND SAFETY OF CERTOLIZUMAB PEGOL FOR THE TREATMENT OF AXIAL SPONDYLOARTHRITIS IN REAL-WORLD CLINICAL PRACTICE IN EUROPE: RESULTS FROM A PROSPECTIVE NON-INTERVENTIONAL 12-MONTH COHORT STUDY. (June 2019) - Baraliakos, Xenofon; Witte, Torsten; Clerck, Luc De; Frediani, Bruno; Collantes-Estévez, Eduardo; Katsifis, Gkikas; Vanlunen, Brenda; Kleine, Elisabeth; Hoepken, Bengt; Goodson, Nicola
Abstract : Background: Certolizumab pegol (CZP) is an Fc-free, PEGylated anti-TNF with an established efficacy and safety profile in axial spondyloarthritis (axSpA) in clinical trial settings. 1 Objectives: To report CZP effectiveness and safety in patients (pts) with axSpA, including ankylosing spondylitis (AS; radiographic axSpA) and non-radiographic (nr-) axSpA subpopulations, in routine clinical practice in Europe. Methods: CIMAX (NCT02354105 ) was a non-interventional multicentre prospective cohort study observing CZP treatment response and safety over 12 months in a real-world clinical cohort of axSpA pts newly prescribed CZP. The primary outcome was change from baseline (CFB) in Bath ankylosing Spondylitis Disease activity index (BASDAI) to Week (Wk) 52 in pts with available data, with additional outcomes pertaining to effectiveness and safety. Outcomes were evaluated for aS and nr-axSpA subpopulations (diagnosed according to local practice). Pts who received ≥1 dose CZP were followed up for adverse events (AEs) (Safety Set [SS]); those with baseline and ≥1 post-baseline BASDAI assessment were included in the effectiveness analyses (Full analysis Set [FAS]). Outcomes are reported using observed case data with no imputation. Results: 682 axSpA pts were enrolled from 101 European sites, of whom 490 (71.8%) completed the study. Of those enrolled, 672 formed the SS (AS: 469; nr-axSpA: 201) and 564 the FAS (AS: 384; nr-axSpA: 179); 2(SS)/1(FAS) pts with unconfirmed aS/nr-axSpA were included in the overall axSpA population. 27.5% (185/672[SS]) axSpA pts had previous anti-TNF exposure (AS: 31.1% [146/469]; nr-axSpA: 18.4% [37/201]). BASDAI data were available for 77.8% (439/564) pts at Wk52. In pts with available data, all clinical outcomes were improved at Wk52 in both subpopulations (Table ). At baseline, the mean BASDAI was 6.1. At Wk52, the mean BASDAI CFB in pts with available data (n=439) was −2.9 (AS: −2.9 [n=301]; nr-axSpA: −2.8 [n=137]). For pts with and without prior anti-TNF exposure, BASDAI at baseline was 6.1 in both groups (n=165 vs n=399, respectively), and at Wk52, the mean BASDAI CFB was −2.6 (n=127) vs −3.0 (n=312) (AS: −2.7 vs −3.0; nr-axSpA: −2.2 vs −3.0). In the SS, 37.9% (255/672) pts experienced aEs; 20.7% (139/672) experienced drug-related aEs and 6.3% (42/672) serious aEs (1.8% [12/672] reported serious infections); these data were comparable between aS and nr-axSpA (Table ). Conclusion: This is the first multicentre European study to evaluate CZP effectiveness and safety in both axSpA subpopulations in routine practice. Improvements were observed in all signs and symptoms in pts who remained on treatment to Wk52; >70% of those enrolled completed the study. No new safety signals were identified following application of CZP to real-world rheumatological practice. References: [1] van der Heijde D. Rheumatology (Oxford)2017;56:1498–509. Acknowledgement: We thank the patients who participated. This study was funded by UCB Pharma, medical writing by Jessica Patel, Costello Medical, UK. Disclosure of interests: Xenofon Baraliakos Grant/research support from: abbVie, Boehringer ingelheim, Bristol-Myers Squibb, Celgene, Centocor, Chugai, Janssen, MSD, Novartis, Pfizer inc, Roche and UCB, Grant/research support from: abbVie, Pfizer, Merck Sharp & Dohme, UCB Pharma, Novartis, Consultant for: abbVie, Bristol-Myers Squibb, Boehringer ingelheim, Celgene, Chugai, Janssen Biologics, Novartis, Pfizer, UCB Pharma, Galapagos, Speakers bureau: abbVie, Chugai, Janssen, Novartis, Pfizer, UCB Pharma, Torsten Witte Consultant for: UCB Pharma, Luc De Clerck Grant/research support from: abbvie, MSD, Roche, Pfizer, Bruno Frediani: None declared, Eduardo Collantes-Estévez Consultant for: UCB Pharma, MSD, abbVie, Novartis, Janssen, Gkikas Katsifis Consultant for: UCB Pharma, Janssen, abbvie, Novartis, MSD, aenorasis, Genesis Pharma, Pfizer, Roche, Brenda VanLunen Employee of: Employee of UCB Pharma, Elisabeth Kleine Employee of: Employee of UCB Pharma, Bengt Hoepken Employee of: Employee of UCB Pharma, Nicola Goodson Grant/research support from: Novartis, Speakers bureau: abbVie, Janssen, UCB Pharma